BLOOD PROFILE, DIGESTIVE ORGAN AND FECAL AMMONIA OF LAYING DUCKS FED BY FERMENTED FEED - Allaily Allaily; Muhammad Ridla; M. Aman Yaman; Agus setiyono; Nahrowi Nahrowi (Buletin Peternakan, 2017)
This study was conducted to determine how the fermented feed effect against blood profile, digestive organ and fecal ammonia of laying ducks. Feed materials were prepared according to laying ducks need as 21% crude protein, then mixed rations already given water until 45% the water content, then anaerobic fermented for 7 days. This study used a completely randomized design with 4 treatments of feed, such as: dry feed, wet feed, wet fermentation feed, and commercial dry feed. Each treatment was repeated 5 times, and each replication was consisted of four laying ducks. Laying duck were 80 heads Indramayu duck at 5 month of old. Blood observations were taken 3 times at 5 months, 6.5 months and 8 months old. Parameters measured were red blood cell (RBC), packed cell volume (PCV) = volume percentage of erythrocytes in the blood, hemoglobin (Hb), white blood cell (WBC), heterophile cell (H), lymphocytes (L), monosit (M) and the ratio of HL. Blood was taken from vena pectoralis vein under duck wings. Observation of digestive organs and fecal ammonia content was at 8 months old of duck. The results showed in pre treatment of the 5 months ducks significantly influenced the PCV and the WBC, but at 6.5 months and 8 months of treatment did not significantly affect blood profile of laying ducks. Digestive organs of liver in fermentation treatment showed  significantly  lower  than  in  controls. The  content  of  fecal ammonia were not significantly different.